Using Story Telling Technique to Improve The Speaking Ability of The Second Year Students of SMK Muhammadiyah 2 Pekanbaru - Br.Batubara, Novita Asmeri Br.Batubara Asmeri; ', Hadriana; ', Syafri K (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This classroom action research was aimed to find out if the story telling technique could improve the speaking skill of the second year students of SMK Muhammadiyah 2 Pekanbaru.The participants were 28 students. The data was collected by using observation sheet,speaking tests, and field notes. The research finding indicated that the application of using story telling technique could improve students’ speaking ability both at the first cycle and second cycle. The result of pre-test shows the average score of students speaking ability was 48.2. It improved to 64.9 on the post-test 1 and 76.1on the post-test 2. It was also proved that applying story telling technique in teaching speaking could improve students’ interest and motivation to speak and share ideas with their friends in groups. In addition, applying story telling technique could also improve students’ ability to speak English in terms of grammar, vocabulary, pronunciation, fluency, and comprehension. Keywords:Story Telling Technique, speaking Ability